Pengelolaan dan Pemberdayaan Wakaf Produktif: Studi Program Wakaf Ternak Lembaga Wakaf Al-Azhar di Bandung - Zuraedah Rahmah, Siti; Munawar, Wildan; Aziz, Imam Abdul (Jurnal Iqtisaduna, 2024)
This study aims to analyse the management and empowerment of productive waqf in the livestock waqf program at Al-Azhar Waqf Institute. The method used in this study is a qualitative descriptive approach with data sourced from primary and secondary data through observation, interviews, books, scientific journals, articles, the internet, and other data or library sources. The analysis technique used is the analysis of Miles and Huberman. The results showed that Al-Azhar’s livestock endowments have four management functions: planning, organising, leadership, and supervisory. Meanwhile, the empowerment of Al-Azhar livestock waqf is carried out through several stages, namely the application of awareness to the community, the formation of organisations, the formation of regeneration, the provision of technical support, and system management. The results of this research can be considered for Al-Azhar waqf institutions to continue managing and developing productive endowments, especially in the livestock sector.